Kinetic assembly of coordination networks. Issue 63 (10th July 2017) - Ohtsu, Hiroyoshi; Kawano, Masaki
Abstract : Kinetic assembly is an important method for obtaining desired materials in chemical synthesis and materials science. Abstract : Kinetic assembly is an important method for obtaining desired materials in chemical synthesis and materials science. We highlight the kinetic assembly of porous coordination networks, which promote the production of interactive pore sites. The interactive pore sites can activate or stabilize guest molecules. The properties of interactive pores are typified by iodine chemisorption and small sulfur encapsulation. Using interactive pores, we trapped small sulfur allotropes, such as S2, cyclo-S3, bent-S3, and S6, demonstrating the importance of interactive pore sites. Here, we address the important aspects of interactive pore sites created by kinetic assembly of porous coordination networks.